Urinary incontinence in women - Aoki, Yoshitaka (Nat Rev Dis Primers, 2017)
Urinary incontinence symptoms are highly prevalent among women, have a substantial effect on health-related quality of life and are associated with considerable personal and societal expenditure. Two main types are described: stress urinary incontinence, in which urine leaks in association with physical exertion, and urgency urinary incontinence, in which urine leaks in association with a sudden compelling desire to void. Women who experience both symptoms are considered as having mixed urinary incontinence. Research has revealed overlapping potential causes of incontinence, including dysfunction of the detrusor muscle or muscles of the pelvic floor, dysfunction of the neural controls of storage and voiding, and perturbation of the local environment within the bladder. A full diagnostic evaluation of urinary incontinence requires a medical history, physical examination, urinalysis, assessment of quality of life and, when initial treatments fail, invasive urodynamics. Interventions can include non-surgical options (such as lifestyle modifications, pelvic floor muscle training and drugs) and surgical options to support the urethra or increase bladder capacity. Future directions in research may increasingly target primary prevention through understanding of environmental and genetic risks for incontinence.